Improved body weight and performance status and reduced serum PGE2 levels after nutritional intervention with a specific medical food in newly diagnosed patients with esophageal cancer or adenocarcinoma of the gastro‐esophageal junction. Issue 1 (31st March 2015) - Faber, Joyce; Uitdehaag, Madeleen J.; Spaander, Manon; van Steenbergen‐Langeveld, Sabine; Vos, Paul; Berkhout, Marloes; Lamers, Cor; Rümke, Hans; Tilanus, Hugo; Siersema, Peter; van Helvoort, Ardy; van der Gaast, Ate
Abstract: Background: The majority of cancer patients loses weight and becomes malnourished during the course of their disease. Metabolic alterations and reduced immune competence lead to wasting and an increased risk of infectious complications. In the present study, the effect of a nutritionally complete medical food, which is high in protein and leucine and enriched with fish oil and specific oligosaccharides, was investigated on immune function, nutritional status, and inflammation in patients with esophageal cancer and compared with routine care. Methods: In this exploratory double‐blind study, 64 newly diagnosed esophageal cancer patients were randomized. All patients received dietary counselling and dietary advice. In the Active group, all patients received the specific medical food for 4 weeks before the start of anticancer therapy. In the routine care control arm, patients with <5% weight loss received a non‐caloric placebo product, and patients with weight loss ≥5% received an iso‐caloric control product to secure blinding of the study. The required study parameters of body weight and performance status were recorded at baseline and after 4 weeks of nutritional intervention, and patients were asked to complete quality of life questionnaires. In addition, blood samples were taken for the measurement of several immune, nutritional, and safety‐parameters. Results: No effect of the specific nutritional intervention could be detected on ex vivo stimulations of blood mononuclear cells. By contrast, body weight was significantly increased ( P  < 0.05) and ECOG performance status was improved after intervention with the specific medical food ( P  < 0.05). In addition, serum Prostaglandin E2 (PGE2 ) levels were significantly decreased in the specific medical food group and increased in the control group ( P  = 0.002). Conclusions: Nutritional intervention with the specific medical food significantly increased body weight and improved performance status compared with routine care in newly diagnosed esophageal cancer patients. This effect was accompanied by significantly reduced serum PGE2 levels.